Symptoms of respiratory tract infection and associated care-seeking in subjects with and without obstructive lung disease; The Tromso Study: Tromso 6. - Melbye, Hasse; Joensen, Lisa; Risør, Mette Bech; Halvorsen, Peder Andreas (BMC Pulmonary Medicine, 2012)
Respiratory tract infections (RTIs) may be more severe in those with asthma or COPD and these patients are more frequently in need of health care. The aim of the study was to describe the frequency of RTI symptoms in a general adult population and how care-seeking is associated with the presence of obstructive lung disease. Cross-sectional data including spirometry and self-reported chronic diseases were collected among middle-aged and elderly subjects in the Tromso population survey (Tromso 6). Self- reported RTI symptoms, consultations and antibiotic use were the main outcome variables. Possible predictors of RTI symptoms were evaluated by multivariable logistic regression. Of the 6414 subjects included, 798 (12.4 %) reported RTI symptoms in the previous week. RTI symptoms were reported less frequently by subjects aged 75 years or above, than by those younger than 55 years (OR 0.5). Winter season (OR 1.28), current smoking (OR 1.60), low self-rated health (OR 1.26) and moderate to severe bronchial obstruction (OR 1.51), were also statistically significant independent predictors of RTI symptoms, but these variables did not predict RTI symptoms that had started within the previous seven days. Among subjects with RTI symptoms, 5.1 % also reported a consultation with a doctor. In those with bronchial obstruction by spirometry, who did not report asthma or COPD, this frequency was 2.4 %. Antibiotic treatment was reported by 7.4 % of the participants, among whom one third had consulted a doctor. Antibiotics were taken more frequently when asthma or COPD was reported (13.7 %), but not in subjects with bronchial obstruction who did not report these diseases (7.2 %). RTI symptoms seldom led to consultation with a doctor and not even in subjects with obstructive lung disease. This was in particular the case in subject who did not know about their obstructive lung disease. Strategies for early diagnosis of COPD and providing health care to subjects with such disease cannot rely on their doctor visits due to respiratory ...